Use effects on the reflection of macro textured surfaces - Ixtaina, Pablo Rubén (2016)
The emergence of led luminaries in street lighting has modified traditional design guidelines. The highest led energy efficiency allows keeping suitable lighting levels with less installed power. Thus, the present design line of a street lighting installation is closely related to the technological change: kind of led to be used, suitable lens, efficacy relationship regarding high pressure sodium, light colour temperature, spectrum. The “impact” associated to with led conversion relegates main aspects of street designs: effect of road reflective properties and installation depreciation. The wear produced by traffic, as well as the environmental conditions gradually modifies the road reflection matrix. In a street lighting installation, this change alters the luminance arrangement on the road together with the perception conditions. This phenomenon is a determining factor within the global concept of depreciation affecting lighting systems in general and also street lighting installations designed by the Luminance Technique. In the present work changes, due to use, in the shape of street reflection matrices of Argentinean highways are analyzed. The analyzed r-tables were obtained through “in-situ” measurements, with road reflectometer. A first group corresponds to the initial conditions of macro textured roads which were measured in the period 2001/2003. The second studied set contains r-tables of the same type, and according to its use the surfaces can be considered in steady state, assessed between 2005 and 2009. The study provides information about the shape of matrixes and its alteration, specularity and scale factor, relating such parameters with the possible effects on the resulting lighting.